Doxofylline ameliorates liver fibrosis by regulating the ferroptosis signaling pathway - Xu, Lenan; Zhang, Meiling; Pan, Junzhi; Xu, Xiangwei; Zhang, Yawen; Han, Xue; Yin, Lina; Chen, Lingfeng; Ren, Juan; Yu, Jie; Zhang, Yanmei; Liang, Guang; et al. (Frontiers in Pharmacology, 2023)
Liver fibrosis, a compensatory repair response to chronic liver injury, is caused by various pathogenic factors, and hepatic stellate cell (HSC) activation and phenotypic transformation are regarded as key events in its progression. Ferroptosis, a novel form of programmed cell death, is also closely related to different pathological processes, including those associated with liver diseases. Here, we investigated the effect of doxofylline (DOX), a xanthine derivative with potent anti-inflammatory activity, on liver fibrosis as well as the associated mechanism. Our results indicated that in mice with CCl4-induced liver fibrosis, DOX attenuated hepatocellular injury and the levels of liver fibrosis indicators, inhibited the TGF-β/Smad signaling pathway, and significantly downregulated the expression of HSC activation markers, both in vitro and in vivo. Furthermore, inducing ferroptosis in activated HSCs was found to be critical for its anti-liver fibrosis effect. More importantly, ferroptosis inhibition using the specific inhibitor, deferoxamine (DFO) not only abolished DOX-induced ferroptosis, but also led to resistance to the anti-liver fibrosis effect of DOX in HSCs. In summary, our results showed an association between the protective effect of DOX against liver fibrosis and HSC ferroptosis. Thus, DOX may be a promising anti-hepatic fibrosis agent.